A Network Analysis of Potential Antecedents and Consequences of Pain-Related Activity Avoidance and Activity Engagement in Adolescents. Issue 2 (9th September 2019) - Beeckman, Melanie; Simons, Laura E; Hughes, Sean; Loeys, Tom; Goubert, Liesbet
Abstract: Objective: This study sets out to identify potential daily antecedents and consequences of pain-related activity avoidance and engagement behavior in adolescents with chronic pain. Methods: Adolescents (N = 65, Mage = 14.41) completed baseline self-reports and a diary for 14 days. Afternoon and evening reports were used to infer a network structure of within-day associations between pain intensity, pain-related fear, pain catastrophizing, affect, and pain-related activity avoidance and engagement behavior. Baseline psychological flexibility was examined as a potential resilience factor. Results: Activity avoidance in the evening was predicted by pain-related fear and avoidance earlier that afternoon. Activity engagement was predicted by positive affect and activity engagement in the afternoon. Pain-related behavior in the afternoon was not related to subsequent changes in pain intensity, pain-related fear, pain catastrophizing, or affect. Pain-related fear in the afternoon was predictive of increased levels of pain and pain catastrophizing in the evening. Both pain-related fear and pain catastrophizing in the evening were predicted by negative affect in the afternoon. Psychological flexibility was associated with lower levels of daily activity avoidance and buffered the negative association between pain intensity and subsequent activity engagement. Conclusions: This study provides insight into unique factors that trigger and maintain activity avoidance and engagement and into the role of psychological flexibility in pediatric pain. Future work should focus on both risk and resilience factors and examine the role of psychological flexibility in chronic pediatric pain in greater detail.